Accounting teacher self effication, usage, teaching preference and skill towards virtual learning environment in education - Ahmad, Noor Lela; Ahamad Rapani, Nor Hanani; Ismail, Zuriadah; Ahmad, Anis Suriati (Science and Engineering Research Support Society, 2020)
The government through the Ministry of Education Malaysia promotes the use of technology in the teaching and learning practices among teachers as medium to connect and supports e-learning activities between students and teachers. Accordingly, this study aimed to explore teachers’ usage of virtual learning environment, assess teachers’ teaching preferences and ICT skills as well as examine the effect of teachers’ self-efficacy towards the use of virtual learning environment. The study used survey methods to collect data. The respondents of the study were selected using a purposive sampling method. 156 accounting teachers from schools in Perak, Kedah and Selangor were selected as the sample. Data were analyzed using descriptive analysis that measured mean values, percentages, frequency and standard deviations. Inference tests involving Pearson Correlation was used to analyze relationships between variables. The findings revealed that teachers tend to favor modern/contemporary learning styles. However, the frequency of use of Frog VLE among teachers is still low while the level of Frog VLE usage among teachers is moderate. The ability of teachers to handle ICT applications in teaching is at moderate level. Furthermore, result showed that there is a significant association between teachers’ self efficacy and the usage of VLE Frog. Therefore, teachers need to be given ongoing training and motivation to promote and improve their skills using the latest technology. Infrastructure facilities in schools need to be enhanced so that the implementation of etechnology learning can encourage effective educational processes.